Implementasi Enterprise Resources Planning Berbasis Odoo Pada Rumah Makan Kluwak Rawon - Ababil, Putri Sabilina; Pratiwi, Dian; Siswanto, Teddy (Jurnal Sistem Informasi, Teknik Informatika dan Teknologi Pendidikan, 2023)
Kluwak Rawon Restaurant is a place to eat that is still classified as Small and Medium Enterprises (SMEs) because its business processes are still done manually, so that financial records and recording of raw material stocks are not recorded properly which makes expenses irregular. In an era that uses this technology a lot, the solution to solving problems like the one above is to implement Enterprise Resources Planning (ERP) at the restaurant. The software used for this ERP implementation is Odoo, because Odoo has the appropriate modules to solve the above problems, such as Purchasing, Inventory, Point Of Sales (POS) modules, Accounting. With the implementation of the ERP system at the restaurant, business processes will be more closely monitored and operations will run more effectively and efficiently, making it profitable for the restaurant.